Technology Transfer and Innovation for Low-Carbon Development - Pigato, Miria (Washington, DC: World Bank, 2020)
Technological revolutions have increased the world’s wealth to a level that was once unimaginable. They have done so unevenly, however, and in ways that have accelerated climate change. Technology Transfer and Innovation for Low-Carbon Development argues that most of the emissions reductions required to achieve the Paris Agreement goals can be reached through the global deployment of existing and commercially proven low-carbon technologies (LCTs). Deploying LCTs from high-income countries—which account for 80 percent of all LCT innovations and 70 percent of all LCT exports—to developing countries, where they are needed most, will not be easy; but the evidence is clear that it can be done. Transferring LCTs is not only necessary to meet the climate targets, but it is also an opportunity to achieve development goals. The policies needed to deploy LCTs to developing countries could raise output and employment while yielding welfare benefits, such as reduced air and water pollution. Moreover, adopting LCT offers an opportunity for countries to benefit from participation in global value chains and to become LCT producers and exporters.